STUDI PENAMBATAN MOLEKULER SENYAWA TURUNAN KAROTENOID SEBAGAI INHIBITOR ALFA GLUKOSIDASE UNTUK KANDIDAT OBAT ANTIDIABETES - Panjaitani, Riong Seulina; Fauzi , Amar Sulthan (Seroja Husada: Jurnal Kesehatan Masyarakat, 2024)
Derivatives of carotenoid groups (Astaxanthin, Neoxanthin, Zeaxanthin, Lutein, and Beta-carotene) can inhibit the function of alpha-glucosidase enzyme Molecular interactions between compounds or ligands and receptors or enzymes can be simulated in silico using molecular docking techniques. Molecular docking simulations are useful for predicting ligand binding free energy values and analyzing ligand-receptor interactions. Docking data is visualized using Molergo docking, PyMol 2.3, and Discovery Studio version 21.1.1. Interaction analysis is performed using Discovery Studio version 21.1.1. and Molergo Docking. Based on the docking results, all five compounds showed interactions with the alpha-glucosidase protein in the same interaction region as acarbose. Some formed residues include TYR360 in zeaxanthin and neoxanthin. Residue RG608 was found in the active site of astaxanthin and lutein. Residue LEU355 was also identified in the active site of neoxanthin with the alpha-glucosidase protein. Residue HIS717 was identified in the active site of beta-carotene, lutein, and neoxanthin. Residue HIS584 was detected in the active site residue of beta-carotene, astaxanthin, and lutein. The active site GLU196 was identified inzeaxanthin and residue PRO595 was also present in beta-carotene. The presence of the same active site residues as acarbose, the control for alpha-glucosidase, indicates that all five target compounds have the potential to act as alpha-glucosidase inhibitors and have the same mechanism as acarbose. Derivatives of carotenoid groups can function as alpha-glucosidase inhibitors in silico.